Ensino das Ciências Naturais nos Círculos de Cultura de Cabo Verde que Adoptam a Pedagogia do Texto - Marçal, Lena Maria Pires Correia Lopes (2006)
This dissertation has as essential purpose to analyse how it is processed the teaching of Natural Sciences in the Basic Education of Adults (EBA), accounting to the conceptions, principles and educative practices developed in that subject. In Cap Vert, Natural Sciences is not taught as an isolated subject in the Basic Education (EB). The Natural Sciences contents are taught in the Integrated Sciences subject, that englobes Geography, History and Natural Sciences. Analysing the teaching practices of this subject in the Cultural Circles was realized the existence of difficulties and limitations on the side of the animators. It is necessary changes that allow to overcome those insufficiencies. One of the alternatives was the use of the PdT approach. Being that way, the privileged places of investigation were the Cultural Circles, that try to develop their educative work, opting for the Pedagogy approach of the Text, an experiment of the General Direction of the Alphabetisation and Education of Adults in Cap Vert. The central question of the investigation is: how is it taught the subject of Natural Sciences in the Cultural Circles of Cap Vert that adopted the Pedagogy of the Text. On the theoric fundamentation of this project, the essential references were of the following authors: Giordan and of Vecchi, that approached the fundamental question of the apprentices conceptions; Fumagalli, that points as strategies of Natural Sciences teaching the existing knowledge of the apprentices; Mugrabi, that gives inputs for a text approach on the teachinglearning processes; Tristão and Amaral, who speak about the practical of the interdesciplinarity and of the environment question as elements that make easy the acquisition of a dispersed and compartmentalized knowledge, and making visible the interactions between the subjects. We use the qualitative methodology. In the research participated three animators that work with the Pedagogy approach of the Text and eighty one apprentices of the third level in the Cultural Circles in the country of Praia. The data collecting instruments were a participant observation grill, and interviews of the animators and apprentices. The collected information was used in the evaluation of the opportunity of the Pedagogy of the Text for the Adults education in Cap Vert.